Optimization of Aceh Low Rank Coal Upgrading Process with Combination of Heating Media to Reduce Water Content through Response Surface Method - Mardhiyah, Fadhilah Al; Mahidin; Fauzi; Faisal Abnisa; Khairil (UIR PRESS, 2024)
This research aims to improve the rank of coal in Aceh, which is known to have a relatively high moisture content of 44-52%. The upgrading process is carried out by using hot water, and hot oil as media combined with microwaves to remove moisture content in coal. The process was carried out using microwave rotary dryer equipment by varying the coal particle size of 10, 20, and 30 mesh, and the time for 20, 40, and 60 minutes. Response surface methodology utilizing the Central Composite Design (CCD) approach was employed to ascertain the optimal conditions for low rank coal, culminating in nine experimental runs involving low rank coal. The validation of the derived quadratic polynomial model has been conducted, yielding a correlation coefficient (R²) value of 0.994. The optimization process aimed at maximizing the moisture content of low rank coal at 4.906 kg, which resulted in a 20% reduction by adjusting the particle size to 5 Mesh M and the duration to 20 minutes, respectively. Consequently, this research is anticipated to serve as a foundational reference for the advancement of coal upgrading methodologies in Aceh, facilitating their transition from laboratory scale to commercial implementation.